Heat transfer augmentation through the use of wire-rod bundles under constant wall heat flux condition - Nanan, K.; Pimsarn, M.; Jedsadaratanachai, W.; Eiamsa-ard, S. (My University, 2013)
This article reports an experimental investigation on heat transfer, friction factor and thermal performance characteristics of turbulent flow (6000. ≤. Re≤. 20,000) in heat exchanger tubes with wire-rod bundles as flow turbulators. The experiments were carried out at three different pitch ratios (P/D) of 1.0, 1.5 and 2.0 and three wire-rod number per bundle (N) of 4, 6 and 8. The experimental results show that Nusselt number increases with increasing Reynolds number and wire-rod number per bundle, and decreasing pitch ratio (P/D) of the turbulators. As compared to the results of the tube without wire-rod (the plain tube), heat transfer rate and friction factor are respectively increased in ranges of 3.5 to 68.8% and 156 to 353%, depending on the operating conditions. At the same pumping power, the use of wire-rod turbulators results in thermal performance factor up to 1.02 times of those of the plain tube. In addition, the correlations that developed from the present experimental data for Nusselt number, friction factor and thermal performance factor are also presented. © 2013 Elsevier Ltd.
Keywords: Friction; Heat transfer enhancement; Turbulator; Turbulence flow; Wire-rod